Non-circular orifice flowfields in valvular regurgitation - Green, Derek W.; Myers, Jerry G.; Anayiotos, Andreas (My University, 1995)
The proximal flowfield (PFF) is a primary tool in quantifying valvular regurgitation when using Color Doppler Ultrasound (CDU) in-vivo. Regurgitant flow calculations are made using the proximal isovelocity surface area (PISA) method and the aliasing technique such that flow rate = V alias*(PISA). However, the actual PFF in non-circular orifices has not been extensively validated. In this study, the PFFs for circular and non-circular orifices are compared in-vitro by Laser Doppler Velocimetry (LDV) and CDU. This comparison defines the details of the PFF, and may prove useful in quantifying valvular regurgitation independent of orifice shape.
Keywords: Biomechanics; Flow meters; Holes